The Effect of Financial Ratios, Maqasid Sharia Index, and Index of Islamic Social Reporting to Profitability of Islamic Bank in Indonesia - Hosen, Muhammad Nadratuzzaman; Jie, Ferry; Muhari, Syafaat; Khairman, Muhammad (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2019)
This study aims to analyze the performance of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Net Income Margin (NIM), Operating Expenses Ratio (OER), Maqasid Sharia Index (MSI), and Index of Islamic Social Reporting (ISR) to influence the level of profitability. The main purpose of this study is to complete the previous research with try to add the variables MSI and Index of ISR to estimating the change of profitability of Islamic banks in Indonesia. The study conducted eight Islamic Banks to be analyzed in the period from 2010 to 2012. The tool of analysis is used multiple linear regression for predicting the level of profitability. The results of the study show that all of the independent variables are significantly affected simultaneously to the level of profitability. Partially, NIM and OER are significantly affected by the level of profitability. The low level of Maqasid Sharia Index and Islamic Social Reporting implementation of the Islamic banks in Indonesia in the period of the study proves that these two variables are not the main indicator or a major achievement of most Islamic banks, even though Islamic banks should refer to attain mashlalah (public interest).Abstrak:Penelitian ini bertujuan untuk menganalisis kinerja yang ditunjukkan oleh rasio Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Net Income Marging (NIM), Biaya Operasional terhadap Pendapatan Operasional (BOPO), Indeks Maqashid Syariah (MSI), dan Indeks Islamic Social Reporting (ISR) terhadap profitabilitas bank syariah di Indonesia. Tujuan dari penelitian ini adalah melengkapi penelitian-penelitian sebelumnya dengan menambahkan variabel MSI dan ISR untuk mengestimasi profitabilitas bank syariah di Indonesia. Penelitian ini menggunakan data tahunan pada delapan bank syariah pada periode antara tahun 2010 hingga 2012 dimana penelitian ini menggunakan metode regresi linier berganda. Hasil penelitian ini menunjukkan bahwa secara simultan seluruh variabel independen mempengaruhi profitabilitas bank syariah secara signifikan. Secara parsial hanya NIM dan BOPO yang berpengaruh signifikan terhadap profitabilitas. Lemahnya pengaruh Indeks Maqashid Syariah dan Indeks Islamic Social Reporting menunjukkan bahwa kedua variabel tersebut bukanlah faktor utama dalam pencapaian bank syariah, meskipun bank syariah juga harus memperhatikan faktor mashlahah.